Implementasi Digital Governance untuk Mewujudkan Good Governance di Provinsi Bali: Studi pada Badan Pusat Statistik, Dinas Komunikasi, Informatika dan Statistik, dan Kantor Imigrasi Kelas 1 TPI Denpasar - Jacika Pifi Nugraheni; Joko Pramono (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The development of information technology encourages local governments to accelerate the implementation of digital governance to realize the principles of Good governance such as transparency, accountability, effectiveness, and efficiency of public services. This study aims to analyze the implementation of digital governance in Bali Province through a study of three agencies: the Central Statistics Agency (BPS) of Bali Province, the Communication and Information Agency (Diskominfos) of Bali Province, and the Denpasar Class I Immigration (TPI). The research method used is qualitative with data collection techniques through question and answer discussions during comparative studies with relevant agency officials, direct observation, and document searches (digital service websites, public dashboards, SPBE). The results show that all three agencies have implemented digitalization in aspects of planning, service, and data integration. BPS utilizes statistical digitalization to support data-based decision-making, Diskominfos acts as an integrator through the Electronic-Based Government System (SPBE), while Immigration applies service digitalization to improve the quality of public services (online queuing system, M-Passport, autogate). Digital governance in Bali has contributed to the implementation of good governance, particularly in terms of data transparency, service effectiveness, and efficiency of bureaucratic processes.  However, challenges remain regarding the interoperability of sectoral data between agencies. This research confirms that the success of digital governance depends not only on technology but also on cross-agency collaboration and institutional commitment to implementing Good governance principles.